DIGITAL ECONOMY - G’afurova Iroda (International Engineering Journal For Research & Development, 2020)
The digital economy is fundamentally different from the traditional economy as it existed during the 20th century when many economic theories were crystallized. As such, traditional theories fail to encapsulate the amorphous, global, oligopolistic, intangible, and knowledge-driven nature of the digital economy as it has taken shape thus far in the 21st century. This article helps to set some basic precepts of the digital economy for a wider audience, particularly in terms of its divergences from the tangible traditional economy, while applying much of the same terminology to situate the differences.